OC-014 Patients With Intramucosal Carcinoma Arising In Barrett's Eosophagus Have Similar Outcomes To Those With High Grade Dysplasia: Data From The United Kingdom Registry. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Fullarton, G; Smart, H; Morris, J; Willert, R; Narayanasamy, R; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: Mucosal neoplasia arising in Barrett's oesophagus (BE) can be treated with combined radiofrequency ablation (RFA) and endoscopic mucosal resection (EMR). Once there is submucosal invasion the risk of lymph node metastases increases and surgery is favoured. High grade dysplasia (HGD) and intramucosal carcinoma (IMC) arising from the mucosal layer in BE are defined as separate entities in the revised Vienna classification (category 4.1 and 4.4 respectively). Methods: We examine prospective data from United Kingdom (UK) registry of patients undergoing RFA/EMR for BE neoplasia over past 5 years to compare outcomes between HGD and IMC patient cohorts. Histological confirmation of HGD or IMC was required on two separate occasions by specialist histopathologists prior to treatment. Before RFA, visible lesions were removed by EMR. Thereafter patients underwent RFA 3 monthly following which biopsies were taken at 12 months for clearance of dysplasia (CR-D) and BE (CR-IM). Twelve month outcomes, frequency of EMR, cancer progression and long term durability in both groups were examined. Results: To date 367 patients with HGD and 125 with IMC have been treated. There is no difference in age, sex, baseline BE length between the 2 groups. EMR prior to RFA is far more prevalent in IMC cohort than HGD patients (78 vs. 45%, P < 0.0001). Patients had an average of 2–3 RFA treatments over 12 months (range 1–6) in both cohorts. Rescue EMR after starting RFA for new lesions was similar in both groups (HGD 7%, IMC 6.5%). CR-D and CR-IM in the HGD cohort was 85 and 69% respectively at 12 months. This was not significantly different in the IMC cohort (86 and 71%, p = 0.7). Overall progression to invasive cancer was not significantly different in either cohort (HGD 4.1%, IMC 7.2%). Kaplan Meir survival statistics did not show any difference in long term durability of successful neoplasia treatment in both groups (p = 0.9, log rank test), median follow up 20 months. Conclusion: We report one of the largest series of patients undergoing endoscopic therapy for IMC arising in BE. Patients with IMC are more likely to have visible lesions that require EMR prior to RFA than those with HGD. However, once all visible lesions are removed, there is no statistical difference in clinical outcomes between the cohorts. Minimally invasive endoscopic therapy with RFA/EMR is a safe and effective treatment in patients with IMC. All collaborators of the UK RFA registry are acknowledged for their contributions to this work Disclosure of Interest: None Declared.